2013
DOI: 10.1007/s10495-013-0959-7
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane-induced apoptosis involves p53 and p38 in melanoma cells

Abstract: In malignant melanoma complex reprogramming of cell death and survival pathways leads to increased chemoresistance and poor longer-term survival. Sulforaphane (SF) is a promising isothiocyanate compound occurring in cruciferous plants with reported antiproliferative and proapoptotic activity in several tumor cell lines including melanoma. In this work we investigated the effects of SF in several melanoma cell lines and fresh melanoma cultivates. We found that SF is cytotoxic and induces mitochondrial, caspase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 32 publications
5
36
0
Order By: Relevance
“…SFN is a diet-derived natural agent, present in cruciferous vegetables, that suppresses cancer formation in several systems [29,50,[58][59][60][61][62]. Previous studies suggest that SFN suppresses survival of melanoma cancer cells via mechanisms that involve induction of apoptosis [34,35]. However, the impact on MCS cells has not been studied.…”
Section: Sfn Treatment Reduces Mcs Cell Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…SFN is a diet-derived natural agent, present in cruciferous vegetables, that suppresses cancer formation in several systems [29,50,[58][59][60][61][62]. Previous studies suggest that SFN suppresses survival of melanoma cancer cells via mechanisms that involve induction of apoptosis [34,35]. However, the impact on MCS cells has not been studied.…”
Section: Sfn Treatment Reduces Mcs Cell Survivalmentioning
confidence: 99%
“…SFN is a particularly appealing as a cancer prevention and treatment agent, as it is highly bioavailable in blood and tissues and has no known side effects [30][31][32][33]. SFN has been shown to modulate the melanoma tumor environment and may be an important prevention/treatment option [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that sulforaphane was a highly potent inducer of phase 2 cytoprotective enzymes and played a role in protecting against carcinogenesis, oxidative stress, and inflammation . Recent studies have suggested that sulforaphane could inhibit tumor growth in various cancer cells . The accumulated evidence discusses mechanisms for the cell‐cycle arrest and apoptosis induction by sulforaphane, as one of the mechanisms; inhibition of histone deacetylase (HDAC) by sulforaphane has been shown in human cancer cells .…”
mentioning
confidence: 99%
“…It was reported that EGCG reduced EZH2 expression levels by increasing proteasomal degradation [121, 122]. In addition, sulforaphane (SFN), a natural tumor-preventing compound extracted from broccoli and other cruciferous vegetables [123] was shown to induce apoptosis in melanoma tumor cells and have significant therapeutic potential in skin cancer [124126]. Previous reports identified that SFN could decrease expression of EZH2 through a proteasome-dependent mechanism [122, 127].…”
Section: Targeting Ezh2 For Cancer Therapymentioning
confidence: 99%